Image of Giant in Mythology of Ob Ugrians and Zabolotny Tatars - M. V. Prokopova; G. Ch. Faizullina; E. N. Ermakova (Научный диалог)
The results of a comparative analysis of the images of giants in the mythological traditions of geographically close unrelated peoples — the Ob Ugrians (Khanty and Mansi) and the Zabolotny Tatars are presented in the article. It is noted that the assimilation and leveling of the features of the giants images in original cultures did not occur, despite the fact that the myths of the West Siberian peoples were subjected to processes of mutual influence. Particular attention is paid to the relationship between the external features and the origin of mythological characters (giants) with the specifics of the geoclimatic landscapes inhabited by the peoples that form the epic. The novelty of the research is seen in the fact that for the first time the genesis, attributes and functions of the mythological heroes of unrelated peoples living in adjacent territories — the Ob Ugrians and the Zabolotny Tatars — are compared. The relevance of the study is due to the fact that the image of a giant has significant prospects in the reconstruction of an ethnic cultural space, since, being one of the most archaic characters in myths, at the same time it remains a part of modern cultural consciousness. The author’s vision of the common and unique features of giants as distinctive characters of the Ob-Ugric and Siberian Tatar mythological systems is presented in the article. The research materials were myths and legends of the peoples of Western Siberia, records of oral stories of the indigenous inhabitants of the region, collected by the authors during field expeditions.